STRATEGI DAKWAH MASYARAKAT SAMIN - Hidayah, Lutfi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
The life of the Samin community has undergone many changes and shifts since they embraced Islam. This paper examines the strategy of implementing da'wah to their community. The implementation of Islamic da'wah has existed among them, which can be seen from Islamic nuances, carried out by Fatayat, Muslimat, TPQ, the Hadrah Art group, and the Selapanan Recitation group. The activity became a forum for the development of Islamic teachings among the community. This paper concludes that the da'wah strategy used by the Samin community is the strategy of preaching bi al-hikmah, namely preaching by looking at the situation and condition of them first so that they do not feel compelled or objected to accepting and implementing Islamic teachings. This strategy is quite appropriate to be applied, because before delivering da'wah, da'i already knew the situation and conditions of them. Through the da'wah strategy mentioned above, they can receive da'wah well so that it has a positive impact on their lives.